New Horizons in Plant-Microbe Interactions - Cerny, Martin; Hýsková, Veronika (Plants (Basel, Switzerland), 2024)
Theophrastus, an ancient Greek philosopher known as the "Father of Botany," was among the first to document plant diseases, establishing an understanding of plant biotic interactions some 2300 years ago [...].